Chapter 37 Neuroscientific Threaths to Free Will - Shepherd, Joshua (Taylor & Francis, 2017)
In this chapter, I review recent work on neuroscientifi c threats to free will. What is it for something to threaten free will? Consider, fi rst, an apparent threat. You are walking in the dark, and a shadow looms in the distance. It certainly appears threatening, but you are not sure. What do you do? You consider the source of the threat (the thing casting the shadow, and you attempt to discover whether the threat is actual (an attacker) or merely apparent (a tree). And if the threat is actual, you attempt to discern what epistemic and behavioral changes are required of you.